Línea de la sonrisa y medidas morfométricas labiales, de un grupo de individuos de población Colombiana - Acevedo Arias, Sandra Milena; Campo Martínez, María Fernanda; González Murillo, Liseth Fernanda (Universidad Antonio Nariño, 2023)
The smile line is an expression related to facial aesthetics. This is an imaginary curve that forms in the mouth when a person smiles and follows the curvature of the lower lip. Its position is essential to achieve natural aesthetic results appropriate to the anatomical characteristics of the patients